Back Cover: Hydrogen‐Intercalated Graphene on SiC as Platform for Hybrid Superconductor Devices (Adv. Quantum Technol. 12/2020). Issue 12 (14th December 2020) - Paschke, Fabian; Birk, Tobias; Forti, Stiven; Starke, Ulrich; Fonin, Mikhail
Abstract : In article number 2000082, Fabian Paschke, Mikhail Fonin and co‐workers report on the atomic‐scale study of electronic properties and the superconducting proximity effect in hydrogen‐intercalated graphene on SiC decorated with epitaxial lead (Pb) islands. Scanning tunneling spectroscopy confirms a quasi‐free‐standing nature of the graphene layer. The variations of the proximity‐induced superconducting gap on graphene are measured as function of spatial position as well as of magnetic field strength. The findings of this study pave the way for the large‐scale fabrication of graphene–superconductor heterostructures, which can be implemented for quantum information processing.